Do All Roads Lead to China?: Scholarship of Chinese Commercial Law in the Past Decade (Part 1) - Wei, Shen; Watters, Casey G. (China review (Hong Kong, China : 1991), 2016)
China's recent development of a modern legal system coupled with unparalleled economic growth have drawn substantial attention from commercial law scholars. This review summarizes Chinese- and English-language commercial law academic literature from the past decade contributed by both Chinese and non-Chinese scholars while discussing their different focuses, approaches, and methodologies. China's use of vague laws that rely upon implementation rules resulted in a substantial proportion of articles focusing on policy discussions and comparison to foreign approaches. Subsequently, a common theme in both Chinese and English literature was transplantation of foreign law. Chinese scholars often took a nationalistic approach, primarily assessing laws on their impact on China, whereas non-Chinese scholars advocated the adoption of foreign laws or legal structures to create clear standards and provide certainty for investors, which in turn is believed to facilitate continued growth of the Chinese economy. The literature is grouped into subject categories, allowing for discussion of important works and representative articles from leaders in their respective fields.